Editorial (1,2026) - Nain, Manjeet Singh (Indian Journal of Extension Education, 2025)
Editorial (January-March, 2026) Global agriculture is experiencing significant localised shifts due to erratic weather patterns and shifting climate conditions. Argentina’s 2025/26 wheat harvest is expected to reach a record of between 27.1 and 27.8 million tons, exceeding the previous 2021/22 record of 22.4 million tons by up to 25%. The Kharif season in India has been the most disrupted in recent years due to an erratic and prolonged southwest monsoon (108% of the long-period average) and October led to widespread submergence, fungal outbreaks, and nutrient leaching in crops like cotton, soybean, and maize. Rising temperatures and humidity in late 2025 have accelerated the spread of invasive pests like the fall armyworm and locusts, as well as fungal diseases such as wheat rust. Reports in 2025 highlight that elevated atmospheric CO2 levels are actively reducing the concentrations of protein, iron, and zinc in staple crops like wheat and rice, threatening food security for vulnerable populations. The agricultural sector faces a "perfect storm" of rising inflation and economic stagnation, leading to flat commodity prices and lower farm incomes despite higher input costs. The current issue (January-March, 2026) comprises a total of 37 manuscripts, including eight research tools, seven research notes, and twenty-two full-length research papers. Social Network Analysis of Role of Institutions in Agriculture and Food Security; Understanding Ecology–Economy Interface; Unveiling Regional Disparities in Makhana Farming; Attitude towards NGOs; Effect of Soybean Digital Farmer Field School; Bibliometric Analysis of Global Research on Nutraceutical Crop ; Socio-Economic Determinants of Agriculture Households in Punjab; Labour Bank-Karshika Karma Sena on the Livelihood of Agricultural Labour Households ; Farmers’ Perceptions of Genetically Improved G3 Rohu Fish Culture; Big Five Personality Predictors of Career Readiness among Agricultural Graduate Students; Composite Fertilizer Management Index among Major Field Crop Growers; Occupational Health Hazards among Women Fish Vendors; Perceived Training Needs of Farm Women on Modern Crop Technologies; Small-scale Farmers’ Willingness to Pay for Extension Services; Farmers’ Knowledge on Nutrition and Nutrition-Sensitive Agriculture; Dietary Diversity and Nutritional Status of the Tribal Women; Factors Associated with Perception and Knowledge about Stubble Management; Coverage of Agricultural Issues in Leading Indian Hindi Dailies; Critical Factors Hindering the Millet Entrepreneurial Sector; Marketing Efficiency and Major Constraints of Protected Cultivation; Climate Change Adaptation Strategies among Livestock Rearers ; Bibliometric Analysis of Global Research on Digital Platforms in Rural Knowledge Transfer were covered in Research Article section. In the research note section- Perceptions on the Selection of Seed Varieties for Paddy Farming; Factors Influencing Farmers’ Adaptive Capacity to Climate Change; Farmer Preparedness and Constraints for Agribusiness Opportunities; Mapping Determinants of Beneficiary Knowledge in TSP; Prioritising Backyard Poultry Bottlenecks; Constraints Faced by Developmental Personnel Concerning Livelihood Programmes and Constraints Affecting the Adoption of Low-Carbon Agricultural Technologies were covered. Additionally, research tools for Entrepreneurial Orientation, Knowledge Test on Papaya Ring Spot Virus Management Practices, Nutrition Literacy Scale, Digital Learning Engagement Scale, Farmers’ Attitude scale towards ICT-Based Agro-Advisory Services, Scale to Assess Dairy Farmers’ Attitudes toward Climate-Resilient Dairy Farming, AgTech-Enabled Market Access Scale for Hi-Tech Agriculture, and Knowledge Test on Pesticide Safety were included. The Scopus cite score during the quarter increased from 1.7 to 2.1 (https://www.scopus.com/sourceid/21100846015). I, on behalf of the editorial board, extend my sincere thanks to all those who directly or indirectly assisted the editorial board. We acknowledge the contribution made by the reviewers by including their names. We acknowledge Ms. ACS publisher for maintaining the timeline. All the expert members of the editorial board and willing contributors are sincerely acknowledged. The support extended by the Executive Council is duly acknowledged. Special thanks are extended to Dr. U.S. Gautam, Dr J.R. Mishra, Dr. Keshava, Dr. Basvaprabhu Jirli, and Dr. Bhanu P. Mishra for their insightful thoughts and guidance. (Manjeet Singh Nain)